1993
DOI: 10.1111/j.1749-6632.1993.tb26132.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Advice on Maternal Weight Gain and Actual Weight Gain Results from the 1988 National Maternal and Infant Health Survey

Abstract: Weight gain advice showed a notable shift for white married mothers during the 1980s, with a large decline in reported advice of less than 22 pounds concomitant with a substantial increase in reported advice of 28 pounds or more. For black married mothers, there was little change in reported advice, except in the proportion of mothers who said they were advised to gain at least 35 pounds, which increased from 2 to 11%. It should be noted that it is not possible to corroborate the information on weight gain adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 2 publications
0
18
2
1
Order By: Relevance
“…The findings among these studies were remarkably similar to those applying the recent IOM guidelines, whereby there was a trend for increasing GWG gain from Asian, Hispanic, Black and White women, with Asian women gaining the least and White women gaining the most (Ademowore, Courey & Kime, 1972; Keppel & Taffel, 1993; Caulfield, Witter & Stoltzfus, 1996; Caulfield, Stoltzfus & Witter, 1998; Hickey et al., 1997; Schieve, Cogswell & Scanlon, 1998; Hardy, 1999; Taffel, Keppel & Jones, 2003; Rosenberg et al., 2005; Stotland et al., 2006; Wells et al., 2006; Ochsenbein-Kollble et al., 2007; Ellerbe et al., 2013; Bentley-Lewis et al., 2014; Sackoff & Yunzal-Butler, 2014). Interestingly, few studies reported minority groups experiencing greater discordant GWG than White women.…”
Section: Resultsmentioning
confidence: 99%
“…The findings among these studies were remarkably similar to those applying the recent IOM guidelines, whereby there was a trend for increasing GWG gain from Asian, Hispanic, Black and White women, with Asian women gaining the least and White women gaining the most (Ademowore, Courey & Kime, 1972; Keppel & Taffel, 1993; Caulfield, Witter & Stoltzfus, 1996; Caulfield, Stoltzfus & Witter, 1998; Hickey et al., 1997; Schieve, Cogswell & Scanlon, 1998; Hardy, 1999; Taffel, Keppel & Jones, 2003; Rosenberg et al., 2005; Stotland et al., 2006; Wells et al., 2006; Ochsenbein-Kollble et al., 2007; Ellerbe et al., 2013; Bentley-Lewis et al., 2014; Sackoff & Yunzal-Butler, 2014). Interestingly, few studies reported minority groups experiencing greater discordant GWG than White women.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in the sample as a whole, the prevalence of receiving weight gain advice was low compared with the estimated 60%-73% of first trimester mothers reporting receiving advice about weight gain in reports even before the 1990 IOM recommendations were released. 22,23 However, other research in diverse patient populations has reported a low level of receipt of practitioner advice about appropriate weight gain. 24 As lack of provider advice in the first trimester is related to excessive gestational weight gain in prospective 14 and cross-sectional studies, 16,22,23 efforts are needed to increase the number of practitioners who advise patients early in pregnancy about appropriate weight gain.…”
Section: Discussionmentioning
confidence: 98%
“…[25][26][27] Potential effect measure modifiers included self-reported importance of losing weight, prepregnancy body mass index (BMI), parity, adequacy of pregnancy weight gain, 28 and race. Race was used in the analysis as a sociological construct and not a genetic factor.…”
Section: Selected Covariatesmentioning
confidence: 99%